2001
DOI: 10.1074/jbc.m103408200
|View full text |Cite
|
Sign up to set email alerts
|

Activation of IκB Kinase by Herpes Simplex Virus Type 1

Abstract: Herpes simplex viruses (HSV) are ubiquitous pathogens causing a variety of diseases ranging from mild illness to severe life-threatening infections. HSV utilize cellular signaling pathways and transcription factors to promote their replication. Here we report that HSV type 1 (HSV-1) induces persistent activation of transcription factor NF-B, a critical regulator of genes involved in inflammation, by activating the IB kinase (IKK) in the early phase of infection. Activated NF-B enhances HSV-1 gene expression. H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

10
91
1

Year Published

2003
2003
2019
2019

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 122 publications
(107 citation statements)
references
References 34 publications
10
91
1
Order By: Relevance
“…In the past, several reports have illustrated the capacity of HSV-1 to trigger NF-B activation following infection (42)(43)(44). A possible role for gD as a trigger in NF-B activation could be predicted, considering that HveA, which acts as a cell receptor for gD binding, activates NF-B through interaction with members of the tumor necrosis factor receptor-associated factor family (28) and following the engagement of its natural ligand, LIGHT (31).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the past, several reports have illustrated the capacity of HSV-1 to trigger NF-B activation following infection (42)(43)(44). A possible role for gD as a trigger in NF-B activation could be predicted, considering that HveA, which acts as a cell receptor for gD binding, activates NF-B through interaction with members of the tumor necrosis factor receptor-associated factor family (28) and following the engagement of its natural ligand, LIGHT (31).…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, it has been shown that HSV-1 infection activates NF-B (42,43). Particularly, it has been recently demonstrated that HSV-1 induces persistent activation of NF-B by activating the I B kinase in the early phase of infection of HEp-2 permissive cells (44). However, little information is available at the molec-ular level on mechanisms participating in this activation.…”
mentioning
confidence: 94%
“…Kinase Assay and Western Blot Analysis-Cell lysates were incubated with anti-IKK␣ antibodies in the presence of 15 l of protein-A-Sepharose at 4°C for 12 h. After washing, endogenous IKK activity was determined using GST-IB␣-(1-54) as substrate (11). For immunoblot analysis, equal amounts of protein (40 g/sample) from HaCaT whole cell extracts were separated by SDS-PAGE, blotted to nitrocellulose, and filters were incubated with polyclonal anti-IB␣/MAD3 (Santa Cruz Biotechnology), anti-IKK␣, or anti-p65 antibodies followed by decoration with peroxidase-labeled anti-mouse or anti-rabbit IgG (ECL, Amersham Biosciences) (11).…”
Section: Methodsmentioning
confidence: 99%
“…HaCaT cell monolayers were infected for 1 h at 37°C with HSV-1 strain F1 at a multiplicity of infection of 10 plaque forming units/ cell, unless stated otherwise. Virus titers were determined by plaque assay or by cytopathic effect 50% (CPE 50% ) assay on confluent VERO cell monolayers (11). Inactivated HSV-1 virus was prepared by exposure to UV light (254-nm wavelength) on ice for 15 min.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation